Manajemen digitalisasi layanan marketing terhadap performa pemasaran agensi PT.Equity Life Indonesia - Ma'na, Petrus; Losak, Lusty Agsar; Rantererung, Corvis L; Tandi, Asrin (ARKA INSTITUTE, 2024)
This study aims to understand the implementation of digital services by customers and agents, and to evaluate the effect of digital marketing usage on service quality at PT. Equity Life Indonesia Makassar branch. A qualitative approach with case study and descriptive research types was used through interviews with eight informants, including the support team, agents, and customers. Data collection was carried out through observation, interviews, and documentation, while data analysis used qualitative descriptive methods. The results of the study show that PT. Equity Life Indonesia has provided digital services such as websites, My Elife, Online Chat WhatsApp, CMS applications for agents, and social media with features that can be used directly by agents and customers. Although many have used digital services, some agents and customers still prefer to get information directly from agents, support teams, and customer service. Agents use social media to prospect and recruit new agents, attract public attention by uploading superior products, proof of claim payments, rewards, agent contests, and other activities that help the company's branding. So, it can be concluded that PT. Equity Life Indonesia has provided comprehensive digital services, which can be accessed and used by agents and customers.